Variability of synphysiological processes in three non-arborescent temperate grasslands - Fóti, Szilvia (Acta Biologica Szegediensis, 2002)
Three plan t communities, a loess, a sand and an old-field grassland showed considerable differences in synphysiological variability during an investigation at the same spatial scale in 2000. The two former are widely distributed in the Carpathian Basin and with the latter the Hungarian non-arborescent, herbaceous vegetation is well represented. To arrive at conclusions on the causes of variability of synphysiological characteristics can be difficult when allowing for both physiological and abiotic variability. On the other hand it was also obvious that stands' or vegetation types' physiological processes reflect changes of abiotic conditions in coefficients of variation which could not be demonstrated in parallel coenological investigations. Coenological responses are much slower than the synphysiological ones. When considering synphysiological data under conditions of good water supply and under severe drought stress a decrease of variability was found in all types in the latter case. This trait seems to be independent of any coenological characteristic.